Increased supply from blood vessels promotes the activation of dormant primordial follicles in mouse ovaries - KOMATSU, Kouji; MASUBUCHI, Satoru (Journal of Reproduction and Development, 2020)
The controlled activation of dormant primordial follicles is important for the maintenance of periodic ovulation. Previous reports have clearly identified the signaling pathway in granulosa cells and oocytes that controls the activation of primordial follicles; however, the exact cue for the in vivo activation of dormant primordial follicles is yet to be elucidated. In this study, we found that almost all activated primordial follicles made contact with blood vessels. Based on this result, we speculated that the contact between primordial follicles and blood vessels may provide a cue for the activation of dormant primordial follicles. To confirm this hypothesis, we attempted to activate dormant primordial follicles within the ovaries by inducing angiogenesis through the use of biodegradable gels containing recombinant vascular endothelial growth factor and in cultured ovarian tissues by increasing the serum concentration within the culture medium. The activation of dormant primordial follicles was promoted in both experiments, and our results indicated that an increase in the supply of the serum component, from new blood vessels formed via angiogenesis, to the dormant primordial follicles is the cue for their in vivo activation. In the ovaries, angiogenesis often occurs during every estrous cycle, and it is therefore likely that angiogenesis is the crucial event that influences the activation of primordial follicles.